MAKNA PANGGILAN DALAM PROFESI MENGAJAR: EKSPLORASI FENOMENOLOGIS PADA GURU YAYASANPENDIDIKAN - Rehan Hayatun Nisa'; Umi Anugerah Izzati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The phenomenon of declining loyalty and professional attachment among foundation teachers indicates a need to deeply understand how they perceive their profession, particularly in relation to their sense of calling, which is believed to play an important role in perseverance, dedication, and long-term commitment. This study aims to explore teachers' subjective experiences in perceiving their work as a calling through an interpretive phenomenological approach. Four teachers and one supervisor were selected through purposive-criterion sampling. Data were collected through semi-structured in-depth interviews and participatory observation over three weeks, then analyzed using the stages of Interpretative Phenomenological Analysis (IPA). Validity was maintained through triangulation of sources and methods, bracketing, and member checking. The results of the study show that teachers interpret teaching as a calling through three dimensions of sense of calling according to Dik and Duffy (2012), namely transcendent summons, meaning and purpose at work, and other-oriented goals and motives. The practical implications of these findings emphasize the need for ongoing support from foundations, such as professional development, improved welfare, and space for reflection for teachers. Keywords: sense of calling, teacher, education foundation